Numerical Simulation of Heat Transfer Characteristics in a Finned Flat-Tube Microchannel Heat Exchanger: Published online: 24/09/2025 - Thanh Hao Nguyen; Tran, Thanh Tinh; Dang, Thanh Trung; Nguyen, Hoang Tuan (Journal of Technical Education Science, 2025)
Heat transfer behaviors of a finned flat-tube microchannel heat exchanger have been numerically simulated. The microchannel device model was computed, designed, and simulated in this work. Water serves as the thermal working fluid for the design model; it has a temperature range from 40, 45, 50, 55 to 60 degrees Celsius and a fixed mass flow rate of 0.028 kg/s within the heat exchanger. The fluid that absorbs heat is air, which flows perpendicular to the heat exchanger’s exterior. The study using COMSOL Multiphysics 6.2 software evaluated the effects of inlet parameters, including the feedwater temperature and mass flow rate, on the heat transfer characteristics of the sample. Numerical simulation results of the heat transfer characteristics of a finned flat-tube microchannel heat exchanger were validated by experimental data. The results demonstrated high cooling effectiveness, a characteristic velocity profile, and vortex formation in the first pass. The simulation model showed good agreement with experimental trends (with an approximately 8% deviation), proving useful for design and optimization while clarifying the operating mechanism and the role of numerical simulation. Key contributions include demonstrating significant cooling effectiveness, with water temperature reducing from 60 °C to below 38.6 °C after six passes. The simulations also revealed a flow velocity distribution consistent with fluid dynamics theory, observed vortex formation at the microchannel inlet and outlet, and noted a non-uniform temperature distribution across the fins.